A petrolatum nanoemulsion, its preparation process and application

CN122582023BActive Publication Date: 2026-10-16GUANGDONG WANGXIANGBAOCHENG IND CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611024286.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-07-10
Publication Date
2026-10-16
Estimated Expiration
2046-07-10

AI Technical Summary

Technical Problem

例如,一些配合了凡士林的化妆品,其乳化体系的颗粒粒径通常较大,例如可能达到400nm以上,这限制了其向角质层的渗透能力,影响了保湿效果的深度和持久性

Benefits of technology

针对传统凡士林乳液因颗粒粗大、稳定性差导致的保湿效果不持久问题,本发明首先利用聚乙烯吡咯烷酮和聚乙二醇对纳米二氧化硅进行表面改性,再将其与氢化卵磷脂、甘油混合形成水相溶液,最后将熔融凡士林加入水相溶液中进行乳化,经高压均质和搅拌熟化后得到具有纳米尺度和粒径分布均匀的凡士林纳米乳液,显著提升了凡士林乳液的保湿持久性、改善肤感及增强稳定性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122582023B_ABST
    Figure CN122582023B_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of nursing supplies, and provides a vaseline nanoemulsion, a preparation process and application thereof. The vaseline nanoemulsion comprises the following steps: dissolving polyvinylpyrrolidone and polyethylene glycol in deionized water to obtain a polymer solution; dispersing nano-silicon dioxide powder in deionized water to obtain a silicon dioxide dispersion solution; dropping the polymer solution into the silicon dioxide dispersion solution, and performing high-speed dispersion and stirring and curing to obtain a modified silicon dioxide dispersion solution; dissolving hydrogenated lecithin and glycerol in deionized water to obtain a mixed solution; adding the modified silicon dioxide dispersion solution into the mixed solution to obtain an aqueous phase solution; adding melted vaseline into the aqueous phase solution to obtain a coarse emulsion; and performing homogenization on the coarse emulsion, and performing stirring and curing to obtain the vaseline nanoemulsion. The vaseline nanoemulsion with nano-scale and uniform particle size distribution is prepared, and the moisturizing durability of the vaseline emulsion is significantly improved, the skin feeling is improved, and the stability is enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of nursing care products technology, and relates to a petrolatum nanoemulsion, its preparation process, and its application. Background Technology

[0002] In the realm of personal skincare and cosmetics, maintaining lasting skin hydration is a core requirement. However, for a long time, many traditional skincare lotions have fallen short of expectations in terms of water retention. Consumers often face the following frustration: after applying lotion, the skin's moisture content initially increases, but this effect only lasts for a short time, significantly decreasing to a low level after a few hours. This lack of lasting moisturizing effect makes it difficult for consumers to achieve the desired long-lasting skincare results, and also results in a failure to achieve the desired return on their time and financial investment. This technological bottleneck restricts further improvements in the product experience.

[0003] While various emulsions in the prior art utilize petrolatum as a moisturizing ingredient, their technical solutions often fail to fully realize petrolatum's potential. For example, some cosmetics incorporating petrolatum typically have large particle sizes in their emulsion systems, potentially exceeding 400 nm. This limits their penetration into the stratum corneum, affecting the depth and duration of their moisturizing effect. Traditional preparation processes, such as simple mechanical stirring or homogenization, may struggle to achieve the refined and stable dispersion of oil-phase components, especially highly viscous substances like petrolatum, resulting in poor emulsion system stability or an oily feel on the skin.

[0004] Therefore, the market urgently needs a skin care lotion that can overcome the above-mentioned defects. The requirements are: first, to significantly increase the skin's moisture content; second, to lock in moisture for a long time and slow down the rate of moisture loss; and third, to potentially promote the penetration of effective ingredients such as petrolatum into the stratum corneum. Summary of the Invention

[0005] To address the shortcomings of existing technologies, the present invention aims to provide a petrolatum nanoemulsion, its preparation process, and its application. The present invention prepares a petrolatum nanoemulsion with nanoscale and uniform particle size distribution, which significantly improves the moisturizing durability, skin feel, and stability of the petrolatum emulsion.

[0006] To achieve this objective, the present invention adopts the following technical solution: In a first aspect, the present invention provides a process for preparing a petrolatum nanoemulsion, the process comprising: S1. Polyvinylpyrrolidone and polyethylene glycol are dissolved in deionized water, and the mixture is stirred and heated to obtain a polymer solution; nano-silica powder is dispersed in deionized water to obtain a silica dispersion. S2. Under stirring conditions, the polymer solution is dropped into the silica dispersion, mixed evenly, and then acid solution is dropped into it to adjust the pH value. Subsequently, the mixture is dispersed at high speed and stirred to mature, thereby obtaining the modified silica dispersion. S3. Hydrogenated lecithin and glycerol are dissolved in deionized water, and the mixture is stirred and heated to obtain a mixed solution; under stirring and heating conditions, the modified silica dispersion is added to the mixed solution, and the mixture is stirred evenly to obtain an aqueous solution; S4. Under stirring and heating conditions, the molten petrolatum is added to the aqueous solution to obtain a crude emulsion; under heating conditions, the crude emulsion is homogenized and stirred to mature to obtain the petrolatum nanoemulsion.

[0007] To address the issue of short-lasting moisturizing effects in traditional petrolatum emulsions due to their large particle size and poor stability, this invention first modifies the surface of nano-silica using polyvinylpyrrolidone and polyethylene glycol. Then, it is mixed with hydrogenated lecithin and glycerin to form an aqueous solution. Finally, molten petrolatum is added to the aqueous solution for emulsification. After homogenization and stirring, a petrolatum nanoemulsion with nanoscale size and uniform particle size distribution is obtained, significantly improving the moisturizing duration, skin feel, and stability of the petrolatum emulsion.

[0008] First, this invention uses polyvinylpyrrolidone (PVP) and polyethylene glycol (PEG) to modify the surface of nano-silica. PVP and PEG are pre-dissolved to form a polymer solution, which is then added dropwise to the nano-silica dispersion. The reaction is carried out under acidic conditions. The two polymer molecules, PVP and PEG, adsorb and entangle on the surface of the silica particles, forming an organic polymer coating layer. PVP has strong adsorption capacity and steric hindrance, while PEG provides good hydrophilicity and compatibility. The combined modification with PVP and PEG results in… The surface properties of silica particles change from hydrophilic to amphiphilic. While retaining some hydrophilic groups, the surface also incorporates hydrophobic segments of organic polymers, resulting in modified silica with a core-shell structure. This organic polymer coating not only enhances the dispersion stability of silica particles in the aqueous phase and prevents them from agglomerating, but also provides them with a suitable hydrophilic-hydrophobic balance. This allows them to adsorb onto the oil-water interface, generating strong steric hindrance that hinders droplet aggregation and coalescence, greatly enhancing the physical stability of the emulsion and enabling it to resist damage caused by temperature changes, centrifugation, and other factors.

[0009] Subsequently, the present invention dissolves hydrogenated lecithin and glycerin in water to form a mixed solution, and then adds a modified silica dispersion to the mixed solution. Hydrogenated lecithin is a highly efficient amphoteric surfactant with good emulsifying properties and biocompatibility. When the modified silica dispersion is mixed with the solution containing hydrogenated lecithin, hydrogen bonds and hydrophobic interactions are generated between the organic polymer protective layer on the surface of the modified silica particles and the hydrogenated lecithin molecules, forming a dense and mechanically strong composite interfacial film at the oil-water interface. The composite interfacial film combines the interfacial adsorption capacity of hydrogenated lecithin and the rigid support of modified silica particles, which can effectively stabilize the petrolatum emulsion droplets in the subsequent high-pressure homogenization process, preventing them from agglomerating and merging, and ultimately achieving long-term stability and excellent moisturizing and penetrating properties of the emulsion.

[0010] Finally, this invention emulsifies molten petrolatum by adding it to an aqueous solution. Petrolatum is a high-viscosity hydrocarbon oil, which is very difficult to emulsify directly, easily forming large droplets, resulting in a greasy feel and poor stability in the product. This invention first heats and melts the petrolatum to reduce its viscosity, then adds it to the aqueous solution under high-speed stirring to achieve preliminary emulsification, forming a crude emulsion. Subsequently, the crude emulsion is homogenized under high pressure under heating conditions. This high-pressure homogenization breaks down the petrolatum droplets into nanoscale particles. At this point, the components in the aqueous solution exert a synergistic effect: hydrogenated lecithin molecules rapidly adsorb onto the newly formed large oil-water interface, effectively reducing interfacial tension and preventing the small droplets from re-aggregating; while modified silica particles are anchored at the oil-water interface, forming a dense, mechanically strong composite interfacial film with the hydrogenated lecithin, making it difficult for the petrolatum nanodroplets to re-aggregate and merge. Furthermore, modified silica particles that are not adsorbed onto the interface and dispersed in the aqueous phase can further impede the Brownian motion of droplets by increasing the viscosity of the aqueous phase and forming a three-dimensional network structure, thereby improving storage stability.

[0011] The petrolatum nanoemulsion prepared by this invention has a droplet size that can reach the nanoscale. The nanoscale petrolatum droplets have a huge specific surface area, which increases the contact area between the petrolatum emulsion droplets and the stratum corneum of the skin. This is conducive to the penetration and utilization of moisturizing ingredients in petrolatum. Unlike large particles, it will not just stay on the skin surface and cause a greasy feeling, thus achieving a long-lasting moisturizing effect. It not only has a high initial water content, but also effectively delays the loss of moisture and maintains the skin's hydration for a long time.

[0012] As a preferred embodiment of the present invention, in S1, the mass ratio of polyvinylpyrrolidone to polyethylene glycol is 2:1 to 3:1, for example, it can be 2.0:1, 2.1:1, 2.2:1, 2.3:1, 2.4:1, 2.5:1, 2.6:1, 2.7:1, 2.8:1, 2.9:1 or 3.0:1, but it is not limited to the listed values. Other unlisted values ​​within this range are also applicable.

[0013] This invention specifically limits the mass ratio of polyvinylpyrrolidone (PVP) to polyethylene glycol (PEG) to 2:1 to 3:1. PVP, as the main component, has carbonyl groups on its molecular chain that form strong hydrogen bonds with the silanol groups on the silica surface, thus firmly anchoring it to the silica particles. PEG is used in relatively small amounts; its flexible long-chain structure extends outwards, forming an effective hydration layer and exerting steric hindrance. Within this ratio range, both the strong adsorption effect of PVP and the steric hindrance effect of PEG can be simultaneously achieved, resulting in a dense and complete organic polymer coating layer on the silica surface. This coating layer endows the modified silica particles with suitable amphiphilicity, enabling them to be stably dispersed in aqueous solutions and stably adsorbed at the oil-water interface.

[0014] When the amount of PEG is too high and the amount of PVP is insufficient, because the adsorption capacity of PEG to the surface of silica is weaker than that of PVP, the excessive amount of PEG is difficult to be fully adsorbed on the surface of silica particles, resulting in a loose organic polymer coating layer structure that is prone to falling off during subsequent high-speed dispersion or heating.

[0015] When the amount of PVP is too high, the amount of PEG is insufficient. Excessive PVP content will cause the surface of silica particles to be covered by a large number of hydrophobic polymer segments, resulting in a decrease in hydrophilicity and an increase in hydrophobicity, which will affect their dispersibility in aqueous solution. In addition, insufficient PEG content will result in insufficient thickness and density of the hydration layer on the surface of silica particles, resulting in a weak steric hindrance effect, which will ultimately affect the long-term storage stability of the emulsion.

[0016] In some optional instances, the temperature at which the polyvinylpyrrolidone, polyethylene glycol, and deionized water are stirred and heated is 40 to 50°C, for example, 40°C, 41°C, 42°C, 43°C, 44°C, 45°C, 46°C, 47°C, 48°C, 49°C, or 50°C, but is not limited to the listed values; other unlisted values ​​within this range are also applicable.

[0017] In some optional instances, the stirring and heating speed of the polyvinylpyrrolidone, polyethylene glycol, and deionized water is 300 to 500 rpm, for example, 300 rpm, 320 rpm, 340 rpm, 360 rpm, 380 rpm, 400 rpm, 420 rpm, 440 rpm, 460 rpm, 480 rpm, or 500 rpm, but is not limited to the listed values; other unlisted values ​​within this range are also applicable.

[0018] In some optional examples, the stirring and heating time of the polyvinylpyrrolidone, polyethylene glycol and deionized water is 40 to 60 minutes, for example, 40 minutes, 42 minutes, 44 minutes, 46 minutes, 48 ​​minutes, 50 minutes, 52 minutes, 54 minutes, 56 minutes, 58 minutes or 60 minutes, but is not limited to the listed values, and other unlisted values ​​within this range are also applicable.

[0019] In some optional examples, the total mass fraction of polyvinylpyrrolidone and polyethylene glycol in the polymer solution is 2 to 3 wt%, for example, it can be 2.0 wt%, 2.1 wt%, 2.2 wt%, 2.3 wt%, 2.4 wt%, 2.5 wt%, 2.6 wt%, 2.7 wt%, 2.8 wt%, 2.9 wt%, or 3.0 wt%, but is not limited to the listed values, and other unlisted values ​​within this range are also applicable.

[0020] In some optional instances, the polyethylene glycol is polyethylene glycol 400.

[0021] As a preferred technical solution of the present invention, in S1, the nano-silica powder is dispersed in deionized water and stirred at a stirring speed of 3000~5000 rpm for 30~40 min to obtain the silica dispersion. The stirring speed can be 3000 rpm, 3200 rpm, 3400 rpm, 3600 rpm, 3800 rpm, 4000 rpm, 4200 rpm, 4600 rpm, 4800 rpm or 5000 rpm, and the stirring time can be 30 min, 31 min, 32 min, 33 min, 34 min, 35 min, 36 min, 37 min, 38 min, 39 min or 40 min, but is not limited to the listed values. Other unlisted values ​​within this range are also applicable.

[0022] In some optional examples, the mass fraction of nano-silica powder in the silica dispersion is 3 to 5 wt%, for example, it can be 3.0 wt%, 3.2 wt%, 3.4 wt%, 3.6 wt%, 3.8 wt%, 4.0 wt%, 4.2 wt%, 4.4 wt%, 4.6 wt%, 4.8 wt%, or 5.0 wt%, but is not limited to the listed values, and other unlisted values ​​within this range are also applicable.

[0023] In a preferred embodiment of the present invention, in step S2, the polymer solution is added dropwise to the silica dispersion at a stirring speed of 500-600 rpm, for example, 500 rpm, 510 rpm, 520 rpm, 530 rpm, 540 rpm, 550 rpm, 560 rpm, 570 rpm, 580 rpm, 590 rpm, or 600 rpm. After the polymer solution has been added, the mixture is stirred for another 10-20 minutes, for example, 10 minutes, 11 minutes, 12 minutes, 13 minutes, 14 minutes, 15 minutes, 16 minutes, 17 minutes, 18 minutes, 19 minutes, or 20 minutes. Then, acid is added dropwise to the resulting mixed solution to adjust its pH value to 5-6, for example, 5.0, 5.1, 5.2, 5.3, 5.4, 5.5, 5.6, 5.7, 5.8, 5.9, or 6.0, but not limited to the listed values; other unlisted values ​​within this range are also applicable.

[0024] When the polymer solution is added dropwise to the silica dispersion, the carbonyl groups on the PVP molecular chains bond with the silanol groups on the silica surface through hydrogen bonding. PEG segments adsorb onto the silica particle surface via ether bonds and extend into the aqueous phase to form a hydration layer, thus creating steric hindrance. Subsequently, the pH is adjusted to a weakly acidic environment. This acidic environment promotes the protonation of the silanol groups on the silica surface, enhancing their electrostatic attraction and hydrogen bonding with the polar groups of the polymer. This results in a more compact spread of the polymer chains on the silica particle surface, improving the stability and density of the organic polymer coating. Ultimately, the hydrophilic silica is transformed into modified silica particles with an amphiphilic surface, enabling stable dispersion in aqueous solutions and adsorption at the oil-water interface.

[0025] In some alternative examples, the total mass ratio of the polyvinylpyrrolidone and the polyethylene glycol to the mass ratio of the nano-silica powder is 1.5:1 to 2.5:1, for example, it can be 1.5:1, 1.6:1, 1.7:1, 1.8:1, 1.9:1, 2.0:1, 2.1:1, 2.2:1, 2.3:1, 2.4:1 or 2.5:1, but is not limited to the listed values, other unlisted values ​​within this range are also applicable.

[0026] This invention specifically limits the total mass ratio of polyvinylpyrrolidone and polyethylene glycol to the mass ratio of nano-silica powder to 1.5:1 to 2.5:1. Within this range, PVP and PEG are sufficient to cover the entire surface of nano-silica, forming a complete and dense organic polymer coating layer through interactions such as hydrogen bonding. This allows the silica to be stably dispersed in the aqueous solution, avoiding its own aggregation, and also to act as a solid particle emulsifier, effectively adsorbing onto the oil-water interface, and synergistically stabilizing the petrolatum emulsion droplets with the subsequently added hydrogenated lecithin.

[0027] When the amount of polyvinylpyrrolidone and polyethylene glycol is too low, they cannot completely cover the entire surface of nano-silica. As a result, there will be a large number of unmodified hydrophilic areas on the silica surface. These exposed silanol groups will not only make the particles more likely to aggregate directly through hydrogen bonding, forming larger secondary particles and affecting dispersion stability, but will also prevent them from effectively migrating and adsorbing at the oil-water interface during subsequent emulsification, making it difficult to effectively prevent the coalescence of petrolatum emulsion droplets.

[0028] When the amounts of polyvinylpyrrolidone (PVP) and polyethylene glycol (PEG) are too high, the excess polymer cannot be completely adsorbed onto the surface of silica particles and instead exists in a free state in the aqueous solution. These free polymer molecules become entangled with the adsorbed polymer chains, inducing bridging flocculation between silica particles and affecting the modification effect. Furthermore, during subsequent emulsification, the free polymer molecules compete with hydrogenated lecithin for adsorption at the oil-water interface, affecting the adsorption of hydrogenated lecithin and severely impacting the dispersion stability of the petrolatum emulsion.

[0029] In some optional instances, the acid solution is a citric acid solution with a mass fraction of 5 to 10 wt%, for example, it may be 5.0 wt%, 5.5 wt%, 6.0 wt%, 6.5 wt%, 7.0 wt%, 7.5 wt%, 8.0 wt%, 8.5 wt%, 9.0 wt%, 9.5 wt%, or 10.0 wt%, but is not limited to the listed values; other unlisted values ​​within this range are also applicable.

[0030] In some optional instances, the high-speed dispersion rotation speed is 5000~8000 rpm, for example, it can be 5000 rpm, 5500 rpm, 6000 rpm, 6500 rpm, 7000 rpm, 7500 rpm or 8000 rpm, but is not limited to the listed values, other unlisted values ​​within this range are also applicable.

[0031] In some optional instances, the high-speed dispersion time is 3 to 5 minutes, for example, it can be 3.0 minutes, 3.2 minutes, 3.4 minutes, 3.6 minutes, 3.8 minutes, 4.0 minutes, 4.2 minutes, 4.4 minutes, 4.6 minutes, 4.8 minutes or 5.0 minutes, but is not limited to the listed values, other unlisted values ​​within this range are also applicable.

[0032] In some optional instances, the stirring and maturation speed is 200 to 300 rpm, for example, 200 rpm, 210 rpm, 220 rpm, 230 rpm, 240 rpm, 250 rpm, 260 rpm, 270 rpm, 280 rpm, 290 rpm or 300 rpm, but is not limited to the listed values, and other unlisted values ​​within this range are also applicable.

[0033] In some optional instances, the stirring and maturation time is 40 to 50 minutes, for example, 40 minutes, 41 minutes, 42 minutes, 43 minutes, 44 minutes, 45 minutes, 46 minutes, 47 minutes, 48 ​​minutes, 49 minutes or 50 minutes, but is not limited to the listed values, and other unlisted values ​​within this range are also applicable.

[0034] As a preferred embodiment of the present invention, in S3, the mass ratio of hydrogenated lecithin to glycerol is 6:1 to 8:1, for example, it can be 6.0:1, 6.2:1, 6.4:1, 6.6:1, 6.8:1, 7.0:1, 7.2:1, 7.4:1, 7.6:1, 7.8:1 or 8.0:1, but it is not limited to the listed values. Other unlisted values ​​within this range are also applicable.

[0035] This invention specifically limits the mass ratio of hydrogenated lecithin to glycerol to 6:1 to 8:1. Within this range, hydrogenated lecithin acts as the primary emulsifier, with a relatively high proportion. During high-pressure homogenization, when petrolatum droplets are broken down into nanoscale particles, hydrogenated lecithin can rapidly adsorb onto the newly formed oil-water interface, effectively reducing interfacial tension and forming an initial interfacial adsorption film. Simultaneously, glycerol, as a small-molecule humectant, can alter the polarity, viscosity, and density of the aqueous solution, promoting the compatibility and dispersion stability of hydrogenated lecithin and modified silica particles in the aqueous solution.

[0036] If the amount of hydrogenated lecithin is too low and the amount of glycerol is relatively high, during the high-pressure homogenization process, when a new oil-water interface is formed, a sufficient number of hydrogenated lecithin molecules are needed to move quickly and adsorb onto the entire oil-water interface. If there is an excess of glycerol, it will increase the viscosity of the aqueous solution, hindering the diffusion and migration of hydrogenated lecithin molecules in the aqueous solution, thus preventing the hydrogenated lecithin molecules from moving quickly to the newly formed oil-water interface. In addition, if the amount of hydrogenated lecithin is too low, the coverage of the newly formed oil-water interface will be incomplete, ultimately resulting in the inability to quickly and effectively reduce the interfacial tension of the oil-water interface. This causes the newly formed nano-oil droplets to re-merge during collisions, making it difficult to obtain nanoemulsions with fine particle size and uniform distribution.

[0037] If the amount of hydrogenated lecithin is too high and the amount of glycerin is relatively low, the excess hydrogenated lecithin cannot be completely adsorbed onto the oil-water interface. A large number of free hydrogenated lecithin molecules exist in the aqueous solution, forming micelles or larger aggregates. These aggregates compete with the modified silica particles for adsorption at the oil-water interface, preventing the modified silica particles from adsorbing and affecting the stability of the oil-water interface. Furthermore, insufficient glycerin will directly affect the moisturizing ability of the final petrolatum nanoemulsion.

[0038] In some optional instances, the temperature at which the hydrogenated lecithin, glycerol, and deionized water are stirred and heated is 70-80°C, for example, 70°C, 71°C, 72°C, 73°C, 74°C, 75°C, 76°C, 77°C, 78°C, 79°C, or 80°C, but is not limited to the listed values; other unlisted values ​​within this range are also applicable.

[0039] In some optional instances, the stirring and heating speed of the hydrogenated lecithin, glycerol and deionized water is 300 to 500 rpm, for example, 300 rpm, 320 rpm, 340 rpm, 360 rpm, 380 rpm, 400 rpm, 420 rpm, 440 rpm, 460 rpm, 480 rpm or 500 rpm, but is not limited to the listed values, and other unlisted values ​​within this range are also applicable.

[0040] In some optional instances, the stirring and heating time of the hydrogenated lecithin, glycerol and deionized water is 20 to 30 minutes, for example, 20 minutes, 21 minutes, 22 minutes, 23 minutes, 24 minutes, 25 minutes, 26 minutes, 27 minutes, 28 minutes, 29 minutes or 30 minutes, but is not limited to the listed values, and other unlisted values ​​within this range are also applicable.

[0041] In some optional instances, the total mass fraction of hydrogenated lecithin and glycerol in the mixed solution is 10 to 20 wt%, for example, it can be 10 wt%, 11 wt%, 12 wt%, 13 wt%, 14 wt%, 15 wt%, 16 wt%, 17 wt%, 18 wt%, 19 wt%, or 20 wt%, but is not limited to the listed values, and other unlisted values ​​within this range are also applicable.

[0042] In a preferred embodiment of the present invention, in step S3, the modified silica dispersion is added to the mixed solution at a stirring speed of 300-500 rpm and a heating temperature of 70-80°C. After the modified silica dispersion has been completely added, stirring and heating continue for 20-30 minutes to obtain the aqueous solution. The stirring speed can be 300 rpm, 320 rpm, 340 rpm, 360 rpm, 380 rpm, 400 rpm, 420 rpm, 440 rpm, or 4... The stirring and heating time can be 60 rpm, 480 rpm, or 500 rpm, and the heating temperature can be 70℃, 71℃, 72℃, 73℃, 74℃, 75℃, 76℃, 77℃, 78℃, 79℃, or 80℃. However, it is not limited to the listed values, and other unlisted values ​​within this range are also applicable.

[0043] The main component of the modified silica dispersion is nano-silica particles coated with a composite polymer of PVP and PEG. The mixed solution includes the small molecule emulsifier hydrogenated lecithin and the humectant glycerin. When the two are mixed, under heating and stirring conditions, hydrogenated lecithin molecules interact with the surface of the modified silica particles. The polar head groups of hydrogenated lecithin form hydrogen bonds with the ether bonds and carbonyl groups in the polymer coating layer on the surface of the modified silica particles, and the hydrophobic segments of hydrogenated lecithin interact with the hydrophobic segments in the polymer coating layer on the surface of the modified silica particles, allowing hydrogenated lecithin molecules to adsorb onto the surface of the modified silica particles.

[0044] Glycerin, as a powerful humectant, contains three hydroxyl groups in its molecule, which can form a strong bond with water molecules through hydrogen bonds. This gives the resulting petrolatum nanoemulsion excellent moisture absorption and retention capabilities, achieving long-lasting moisturizing effects. Furthermore, the addition of glycerin promotes the compatibility and dispersion stability of hydrogenated lecithin and modified silica particles in the aqueous solution, allowing hydrogenated lecithin molecules to migrate more freely and contributing to the uniform distribution of modified silica particles, preventing their aggregation. During the subsequent high-pressure homogenization process, when the petrolatum droplets are broken down into nanoscale particles, it ensures that the hydrogenated lecithin and modified silica particles can quickly coat the newly formed oil-water interface.

[0045] In some optional examples, the mass ratio of the modified silica dispersion to the mixed solution is 2:1 to 4:1, for example, it can be 2.0:1, 2.2:1, 2.4:1, 2.6:1, 2.8:1, 3.0:1, 3.2:1, 3.4:1, 3.6:1, 3.8:1 or 4.0:1, but is not limited to the listed values, other unlisted values ​​within this range are also applicable.

[0046] This invention specifically limits the mass ratio of modified silica dispersion to mixed solution to 2:1 to 4:1. Within this range, sufficient modified silica particles are added to the aqueous solution, allowing them to work together with hydrogenated lecithin at the subsequently formed oil-water interface. Hydrogenated lecithin, as a small-molecule emulsifier, can rapidly adsorb and reduce interfacial tension, which is beneficial for the initial formation of the emulsion. Meanwhile, sufficient modified silica particles can be embedded in the oil-water interface film, significantly enhancing the mechanical strength of the interface film. This results in a final oil-water interface film that combines the low interfacial tension of hydrogenated lecithin with the mechanical stability of modified silica particles, effectively resisting the coalescence of petrolatum emulsion droplets.

[0047] When the amount of modified silica dispersion is too low, the amount of modified silica added is insufficient. During emulsification, the oil-water interface mainly relies on the monomolecular interfacial film formed by hydrogenated lecithin to achieve stable dispersion of droplets. Although this interfacial film has good flexibility, its mechanical strength is insufficient, and its physical barrier to droplet aggregation is poor. During long-term storage or temperature changes, the emulsion system is not stable enough, and the size of the emulsion droplets tends to increase over time, affecting the shelf life and performance of the product.

[0048] When the amount of modified silica dispersion is too high, the excess modified silica particles will agglomerate in the aqueous solution, affecting dispersibility. In addition, the excess modified silica particles will excessively occupy the oil-water interface, competitively repelling the adsorption of hydrogenated lecithin at the oil-water interface, resulting in a decrease in the amount of hydrogenated lecithin adsorbed at the oil-water interface, which is not conducive to the initial refinement of the emulsion.

[0049] As a preferred technical solution of the present invention, in S4, the melting temperature of the petroleum jelly is 70~80℃, for example, it can be 70℃, 71℃, 72℃, 73℃, 74℃, 75℃, 76℃, 77℃, 78℃, 79℃ or 80℃, but it is not limited to the listed values. Other unlisted values ​​within this range are also applicable.

[0050] In some optional instances, the melting time of the petroleum jelly is 20 to 30 minutes, for example, 20 minutes, 21 minutes, 22 minutes, 23 minutes, 24 minutes, 25 minutes, 26 minutes, 27 minutes, 28 minutes, 29 minutes or 30 minutes, but is not limited to the listed values, and other unlisted values ​​within this range are also applicable.

[0051] In some optional examples, molten petroleum jelly is added to the aqueous solution at a stirring speed of 3000-5000 rpm and a heating temperature of 70-80°C. After all the petroleum jelly has been added, stirring and heating are continued for 5-10 minutes to obtain the crude emulsion. The stirring speed can be 3000 rpm, 3200 rpm, 3400 rpm, 3600 rpm, 3800 rpm, 4000 rpm, 4200 rpm, 4400 rpm, 4600 rpm, or 4800 rpm. The heating speed can be 5000 rpm or pm, and the heating temperature can be 70℃, 71℃, 72℃, 73℃, 74℃, 75℃, 76℃, 77℃, 78℃, 79℃ or 80℃. The stirring and heating time can be 5.0 min, 5.5 min, 6.0 min, 6.5 min, 7.0 min, 7.5 min, 8.0 min, 8.5 min, 9.0 min, 9.5 min or 10.0 min, but is not limited to the listed values. Other unlisted values ​​within this range are also applicable.

[0052] During emulsification, the oil phase (molten petrolatum) is initially dispersed in an aqueous solution containing hydrogenated lecithin, glycerol, and modified silica particles. When the molten petrolatum is added to the aqueous solution under high-speed stirring, the strong shear force tears the oil phase into larger droplets. Hydrogenated lecithin molecules in the aqueous solution, due to their amphiphilic nature, rapidly migrate to the newly formed oil-water interface, reducing interfacial tension through adsorption and preventing rapid droplet coalescence. Simultaneously, the modified silica particles also migrate to the oil-water interface under shear force, interacting with the hydrogenated lecithin through hydrogen bonds to form a composite interfacial film.

[0053] The crude emulsion was subjected to high-pressure homogenization under heating conditions. This heating ensured that the petrolatum remained in a molten, low-viscosity state, significantly reducing the cohesive force of the oil phase and making it easier to break down under high-pressure homogenization. Simultaneously, heating enhanced the thermal motion of the molecules in each component, promoting the adsorption and alignment of hydrogenated lecithin molecules and modified silica particles at the oil-water interface. Finally, stirring and aging were performed. During this process, more hydrogenated lecithin and modified silica particles filled the gaps in the composite interfacial film, improving the integrity and mechanical strength of the interfacial film.

[0054] In some optional instances, the mass ratio of the petroleum jelly to the aqueous solution is 1:10 to 1:20, for example, 1:10, 1:11, 1:12, 1:13, 1:14, 1:15, 1:16, 1:17, 1:18, 1:19 or 1:20, but is not limited to the listed values; other unlisted values ​​within this range are also applicable.

[0055] This invention specifically limits the mass ratio of petrolatum to aqueous solution to 1:10 to 1:20. Within this range, the aqueous phase dominates as the continuous phase, forming an oil-in-water emulsion that meets the requirements of personal care products for a refreshing feel. Simultaneously, this ratio ensures that the pre-added hydrogenated lecithin and modified silica particles in the aqueous solution are present in sufficient quantities to form a dense and robust composite interfacial film at the newly formed large oil-water interface.

[0056] When the proportion of the aqueous solution is too low, meaning the proportion of petrolatum is relatively high, the oil-water interface area requiring emulsification increases dramatically. The hydrogenated lecithin and modified silica particles in the aqueous solution cannot completely cover all oil-water interfaces, resulting in defects and insufficient strength in the composite interfacial film at the oil-water interface. This significantly increases the risk of droplet aggregation after homogenization, ultimately leading to a product with coarse and unevenly distributed emulsion particles. Furthermore, an excessively high petrolatum content inevitably results in a thick, greasy texture and a poor skin feel in the final product.

[0057] When the proportion of aqueous solution is too high, that is, the proportion of petrolatum is relatively low, the content of effective petrolatum ingredients in the product will be insufficient, making it difficult to form a continuous moisturizing film on the skin surface, which significantly affects the core moisturizing function of the product.

[0058] As a preferred technical solution of the present invention, in S4, the homogenization of the crude emulsion is high-pressure homogenization, and the pressure of the high-pressure homogenization is 80~120MPa, for example, it can be 80MPa, 85MPa, 90MPa, 95MPa, 100MPa, 105MPa, 110MPa, 115MPa or 120MPa, but it is not limited to the listed values. Other unlisted values ​​within this range are also applicable.

[0059] In some alternative instances, the homogenization temperature of the crude emulsion is 40 to 50°C, for example, 40°C, 41°C, 42°C, 43°C, 44°C, 45°C, 46°C, 47°C, 48°C, 49°C or 50°C, but is not limited to the listed values; other unlisted values ​​within this range are also applicable.

[0060] In some optional instances, the crude emulsion is homogenized 3 to 5 times, for example, 3, 4 or 5 times, but not limited to the listed values; other unlisted values ​​within this range are also applicable.

[0061] In some alternative instances, the stirring and maturation temperature is 20-30°C, for example, 20°C, 21°C, 22°C, 23°C, 24°C, 25°C, 26°C, 27°C, 28°C, 29°C or 30°C, but is not limited to the listed values; other unlisted values ​​within this range are also applicable.

[0062] In some optional instances, the stirring and maturation speed is 200 to 300 rpm, for example, 200 rpm, 210 rpm, 220 rpm, 230 rpm, 240 rpm, 250 rpm, 260 rpm, 270 rpm, 280 rpm, 290 rpm or 300 rpm, but is not limited to the listed values, and other unlisted values ​​within this range are also applicable.

[0063] In some optional instances, the stirring and maturation time is 2 to 4 hours, for example, 2.0 hours, 2.2 hours, 2.4 hours, 2.6 hours, 2.8 hours, 3.0 hours, 3.2 hours, 3.4 hours, 3.6 hours, 3.8 hours, or 4.0 hours, but is not limited to the listed values; other unlisted values ​​within this range are also applicable.

[0064] Secondly, the present invention provides a petrolatum nanoemulsion, which is prepared using the preparation process described in the first aspect.

[0065] Thirdly, the present invention provides an application of the petrolatum nanoemulsion described in the second aspect in the preparation of personal care products, the personal care products including body care products and facial care products.

[0066] Compared with the prior art, the beneficial effects of the present invention are as follows: To address the issue of short-lasting moisturizing effects in traditional petrolatum emulsions due to their large particle size and poor stability, this invention first modifies the surface of nano-silica using polyvinylpyrrolidone and polyethylene glycol. Then, it mixes this modified silica with hydrogenated lecithin and glycerin to form an aqueous solution. Finally, molten petrolatum is added to the aqueous solution for emulsification. After high-pressure homogenization and stirring, a petrolatum nano-emulsion with nanoscale size and uniform particle size distribution is obtained, significantly improving the long-lasting moisturizing effect, skin feel, and stability of the petrolatum emulsion. Attached Figure Description

[0067] Figure 1 A process flow diagram for preparing petrolatum nanoemulsion provided by the present invention; Figure 2 This is a particle size distribution diagram of the petrolatum nanoemulsion prepared in Example 1 of the present invention; Figure 3 This is a transmission electron microscope image of the petrolatum nanoemulsion prepared in Example 1 of the present invention. Detailed Implementation

[0068] The technical solutions of the present invention will be described in detail below with reference to specific embodiments and accompanying drawings. The embodiments described herein are specific implementations of the present invention, used to illustrate the concept of the present invention; these descriptions are explanatory and exemplary, and should not be construed as limiting the implementation methods or the scope of protection of the present invention. In addition to the embodiments described herein, those skilled in the art can employ other obvious technical solutions based on the content disclosed in the claims and specification of this application. These technical solutions include those that make any obvious substitutions and modifications to the embodiments described herein.

[0069] Example 1 This embodiment provides a preparation process for a petrolatum nanoemulsion, such as... Figure 1 As shown, the preparation process specifically includes the following steps: S1. Polyvinylpyrrolidone and polyethylene glycol 400 are dissolved in deionized water at a mass ratio of 2:1. The solution is heated at 40°C and 300 rpm for 60 min to obtain a polymer solution. The total mass fraction of polyvinylpyrrolidone and polyethylene glycol 400 in the polymer solution is 2 wt%. Nano-silica powder was dispersed in deionized water and stirred at 3000 rpm for 40 min to obtain a silica dispersion. The mass fraction of nano-silica powder in the silica dispersion was 3 wt%. S2. At a stirring speed of 500 rpm, the polymer solution is dropped into the silica dispersion. The total mass ratio of polyvinylpyrrolidone and polyethylene glycol 400 to the mass ratio of nano silica powder is 1.5:1. After all the polymer solution has been added, continue mixing and stirring for 20 min. Add 5 wt% citric acid solution to the resulting mixed solution to adjust its pH value to 6. Then, stir at high speed of 5000 rpm for 5 min. Finally, stir and mature at 200 rpm for 50 min to obtain the modified silica dispersion. S3. Dissolve hydrogenated lecithin and glycerol in deionized water at a mass ratio of 6:1. Heat and stir at 70°C and 300 rpm for 30 minutes to obtain a mixed solution. The total mass fraction of hydrogenated lecithin and glycerol in the mixed solution is 10 wt%. The modified silica dispersion was added to the mixed solution at a stirring speed of 300 rpm and a heating temperature of 70°C. The mass ratio of the modified silica dispersion to the mixed solution was 2:1. After the modified silica dispersion was completely added, the mixture was stirred and heated for another 30 minutes to obtain an aqueous solution. S4. Melt the petroleum jelly at 70°C for 30 minutes. Add the melted petroleum jelly to the aqueous solution at a stirring speed of 3000 rpm and a heating temperature of 70°C. The mass ratio of petroleum jelly to aqueous solution is 1:10. After all the petroleum jelly has been added, continue stirring and heating for 10 minutes to obtain a crude emulsion. The crude emulsion was subjected to high-pressure homogenization five times at a heating temperature of 40℃ and a homogenization pressure of 80MPa. It was then cooled to 20℃ and stirred and matured at a stirring speed of 200rpm for 4h to obtain the petrolatum nanoemulsion.

[0070] Figure 2 This is a particle size distribution diagram of the petrolatum nanoemulsion prepared in this embodiment. Figure 3 The image shows a transmission electron microscope (TEM) image of the petrolatum nanoemulsion prepared in this embodiment. As can be seen from the image, the droplet size distribution of the petrolatum nanoemulsion prepared in this embodiment is concentrated at around 100 nm, and the particle size distribution is relatively uniform.

[0071] Example 2 This embodiment provides a preparation process for a petrolatum nanoemulsion, such as... Figure 1 As shown, the preparation process specifically includes the following steps: S1. Polyvinylpyrrolidone and polyethylene glycol 400 were dissolved in deionized water at a mass ratio of 2.2:1. The solution was heated at 42°C and 350 rpm for 55 minutes to obtain a polymer solution. The total mass fraction of polyvinylpyrrolidone and polyethylene glycol 400 in the polymer solution was 2.2 wt%. Nano-silica powder was dispersed in deionized water and stirred at 3500 rpm for 38 min to obtain a silica dispersion. The mass fraction of nano-silica powder in the silica dispersion was 3.5 wt%. S2. At a stirring speed of 520 rpm, the polymer solution was dropped into the silica dispersion. The total mass ratio of polyvinylpyrrolidone and polyethylene glycol 400 to the mass ratio of nano silica powder was 1.8:1. After all the polymer solution was added, the mixture was stirred for 18 min. 6 wt% citric acid solution was added to the resulting mixture to adjust its pH to 5.8. Then, the mixture was stirred at a high speed of 6000 rpm for 4.5 min. Finally, it was stirred and matured at a speed of 220 rpm for 48 min to obtain the modified silica dispersion. S3. Hydrogenated lecithin and glycerol were dissolved in deionized water at a mass ratio of 6.5:1. The solution was heated at 72°C and 350 rpm for 28 minutes to obtain a mixed solution. The total mass fraction of hydrogenated lecithin and glycerol in the mixed solution was 12 wt%. The modified silica dispersion was added to the mixed solution at a stirring speed of 350 rpm and a heating temperature of 72°C. The mass ratio of the modified silica dispersion to the mixed solution was 2.5:1. After the modified silica dispersion was completely added, the mixture was stirred and heated for another 28 minutes to obtain an aqueous solution. S4. Melt petroleum jelly at 72°C for 28 minutes. Add the melted petroleum jelly to the aqueous solution at a stirring speed of 3500 rpm and a heating temperature of 72°C. The mass ratio of petroleum jelly to aqueous solution is 1:12. After all the petroleum jelly has been added, continue stirring and heating for 8 minutes to obtain a crude emulsion. The crude emulsion was subjected to high-pressure homogenization four times at a heating temperature of 42℃ and a homogenization pressure of 90MPa. It was then cooled to 22℃ and stirred and matured at a stirring speed of 220rpm for 3.5h to obtain the petrolatum nanoemulsion.

[0072] Example 3 This embodiment provides a preparation process for a petrolatum nanoemulsion, such as... Figure 1 As shown, the preparation process specifically includes the following steps: S1. Polyvinylpyrrolidone and polyethylene glycol 400 are dissolved in deionized water at a mass ratio of 2.5:1. The solution is heated at 45°C and 400 rpm for 50 min to obtain a polymer solution. The total mass fraction of polyvinylpyrrolidone and polyethylene glycol 400 in the polymer solution is 2.5 wt%. Nano-silica powder was dispersed in deionized water and stirred at 4000 rpm for 35 min to obtain a silica dispersion. The mass fraction of nano-silica powder in the silica dispersion was 4 wt%. S2. At a stirring speed of 550 rpm, the polymer solution is dropped into the silica dispersion. The total mass ratio of polyvinylpyrrolidone and polyethylene glycol 400 to the mass ratio of nano silica powder is 2:1. After all the polymer solution has been added, continue mixing and stirring for 15 min. Add 7 wt% citric acid solution to the resulting mixed solution to adjust its pH value to 5.5. Then, stir at a high speed of 6000 rpm for 4 min. Finally, stir and mature at a speed of 250 rpm for 45 min to obtain the modified silica dispersion. S3. Hydrogenated lecithin and glycerol were dissolved in deionized water at a mass ratio of 7:1. The solution was heated at 75°C and 400 rpm for 25 minutes to obtain a mixed solution. The total mass fraction of hydrogenated lecithin and glycerol in the mixed solution was 15 wt%. The modified silica dispersion was added to the mixed solution at a stirring speed of 400 rpm and a heating temperature of 75°C. The mass ratio of the modified silica dispersion to the mixed solution was 3:1. After the modified silica dispersion was completely added, the mixture was stirred and heated for another 25 minutes to obtain an aqueous solution. S4. Melt petroleum jelly at 75°C for 25 minutes. Add the melted petroleum jelly to the aqueous solution at a stirring speed of 4000 rpm and a heating temperature of 75°C. The mass ratio of petroleum jelly to aqueous solution is 1:15. After all the petroleum jelly has been added, continue stirring and heating for 7 minutes to obtain a crude emulsion. The crude emulsion was subjected to high-pressure homogenization four times at a heating temperature of 45°C and a homogenization pressure of 100 MPa. It was then cooled to 25°C and stirred and matured at a stirring speed of 250 rpm for 3 hours to obtain the petrolatum nanoemulsion.

[0073] Example 4 This embodiment provides a preparation process for a petrolatum nanoemulsion, such as... Figure 1 As shown, the preparation process specifically includes the following steps: S1. Polyvinylpyrrolidone and polyethylene glycol 400 were dissolved in deionized water at a mass ratio of 2.8:1. The solution was heated at 48°C and 450 rpm for 45 minutes to obtain a polymer solution. The total mass fraction of polyvinylpyrrolidone and polyethylene glycol 400 in the polymer solution was 2.8 wt%. Nano-silica powder was dispersed in deionized water and stirred at 4500 rpm for 32 min to obtain a silica dispersion. The mass fraction of nano-silica powder in the silica dispersion was 4.5 wt%. S2. At a stirring speed of 580 rpm, the polymer solution was dropped into the silica dispersion. The total mass ratio of polyvinylpyrrolidone and polyethylene glycol 400 to the mass ratio of nano silica powder was 2.2:1. After all the polymer solution was added, the mixture was stirred for 12 min. 8 wt% citric acid solution was added to the resulting mixture to adjust its pH to 5.2. Then, the mixture was stirred at a high speed of 7000 rpm for 3.5 min. Finally, it was stirred and matured at a speed of 280 rpm for 42 min to obtain the modified silica dispersion. S3. Hydrogenated lecithin and glycerol were dissolved in deionized water at a mass ratio of 7.5:1. The solution was heated at 78°C and 450 rpm for 22 min to obtain a mixed solution. The total mass fraction of hydrogenated lecithin and glycerol in the mixed solution was 18 wt%. The modified silica dispersion was added to the mixed solution at a stirring speed of 450 rpm and a heating temperature of 78°C. The mass ratio of the modified silica dispersion to the mixed solution was 3.5:1. After the modified silica dispersion was completely added, the mixture was stirred and heated for 22 min to obtain an aqueous solution. S4. Melt the petroleum jelly at 78°C for 22 minutes. Add the melted petroleum jelly to the aqueous solution at a stirring speed of 4500 rpm and a heating temperature of 78°C. The mass ratio of petroleum jelly to aqueous solution is 1:18. After all the petroleum jelly has been added, continue stirring and heating for 6 minutes to obtain a crude emulsion. The crude emulsion was subjected to high-pressure homogenization three times at a heating temperature of 48°C and a homogenization pressure of 110 MPa. It was then cooled to 28°C and stirred and matured at a stirring speed of 280 rpm for 2.5 h to obtain the petrolatum nanoemulsion.

[0074] Example 5 This embodiment provides a preparation process for a petrolatum nanoemulsion, such as... Figure 1 As shown, the preparation process specifically includes the following steps: S1. Polyvinylpyrrolidone and polyethylene glycol 400 are dissolved in deionized water at a mass ratio of 3:1. The solution is heated at 50°C and 500 rpm for 40 minutes to obtain a polymer solution. The total mass fraction of polyvinylpyrrolidone and polyethylene glycol 400 in the polymer solution is 3 wt%. Nano-silica powder was dispersed in deionized water and stirred at 5000 rpm for 30 min to obtain a silica dispersion. The mass fraction of nano-silica powder in the silica dispersion was 5 wt%. S2. At a stirring speed of 600 rpm, the polymer solution is dropped into the silica dispersion. The total mass ratio of polyvinylpyrrolidone and polyethylene glycol 400 to the mass ratio of nano silica powder is 2.5:1. After all the polymer solution has been added, continue mixing and stirring for 10 min. Add 10 wt% citric acid solution to the resulting mixed solution to adjust its pH value to 5. Then, stir at high speed of 8000 rpm for 3 min. Finally, stir and mature at 300 rpm for 40 min to obtain the modified silica dispersion. S3. Dissolve hydrogenated lecithin and glycerol in deionized water at a mass ratio of 8:1. Heat and stir at 80°C and 500 rpm for 20 minutes to obtain a mixed solution. The total mass fraction of hydrogenated lecithin and glycerol in the mixed solution is 20 wt%. At a stirring speed of 500 rpm and a heating temperature of 80°C, the modified silica dispersion was added to the mixed solution. The mass ratio of the modified silica dispersion to the mixed solution was 4:1. After the modified silica dispersion was completely added, the stirring and heating continued for 20 minutes to obtain an aqueous solution. S4. Melt petroleum jelly at 80°C for 20 minutes. Add the melted petroleum jelly to the aqueous solution at a stirring speed of 5000 rpm and a heating temperature of 80°C. The mass ratio of petroleum jelly to aqueous solution is 1:20. After all the petroleum jelly has been added, continue stirring and heating for 5 minutes to obtain a crude emulsion. The crude emulsion was subjected to high-pressure homogenization three times at a heating temperature of 50°C and a homogenization pressure of 120 MPa. It was then cooled to 30°C and stirred and matured at a stirring speed of 300 rpm for 2 hours to obtain the petrolatum nanoemulsion.

[0075] Comparative Example 1 This comparative example provides a process for preparing petrolatum nanoemulsion. The difference from Example 1 is that in S1, the mass ratio of polyvinylpyrrolidone and polyethylene glycol 400 is adjusted to 1:1, while other operating parameters and process steps are exactly the same as in Example 1.

[0076] Comparative Example 2 This comparative example provides a process for preparing petrolatum nanoemulsion. The difference from Example 1 is that in S1, the mass ratio of polyvinylpyrrolidone and polyethylene glycol 400 is adjusted to 4:1, while other operating parameters and process steps are exactly the same as in Example 1.

[0077] Comparative Example 3 This comparative example provides a process for preparing petrolatum nanoemulsion. The difference from Example 1 is that in S2, the total mass ratio of polyvinylpyrrolidone and polyethylene glycol 400 to the mass ratio of nano silica powder is adjusted to 1:1. Other operating parameters and process steps are exactly the same as in Example 1.

[0078] Comparative Example 4 This comparative example provides a process for preparing petrolatum nanoemulsion. The difference from Example 1 is that in S2, the total mass ratio of polyvinylpyrrolidone and polyethylene glycol 400 to the mass ratio of nano silica powder is adjusted to 3:1. Other operating parameters and process steps are exactly the same as in Example 1.

[0079] Comparative Example 5 This comparative example provides a process for preparing petrolatum nanoemulsion. The difference from Example 1 is that in S3, the mass ratio of hydrogenated lecithin to glycerol is adjusted to 5:1, while other operating parameters and process steps are exactly the same as in Example 1.

[0080] Comparative Example 6 This comparative example provides a preparation process for petrolatum nanoemulsion. The difference from Example 1 is that in S3, the mass ratio of hydrogenated lecithin to glycerol is adjusted to 10:1, while other operating parameters and process steps are exactly the same as in Example 1.

[0081] Comparative Example 7 This comparative example provides a preparation process for petrolatum nanoemulsion. The difference from Example 1 is that in S3, the mass ratio of modified silica dispersion to mixed solution is adjusted to 1:1, while other operating parameters and process steps are exactly the same as in Example 1.

[0082] Comparative Example 8 This comparative example provides a preparation process for petrolatum nanoemulsion. The difference from Example 1 is that in S3, the mass ratio of modified silica dispersion to mixed solution is adjusted to 5:1, while other operating parameters and process steps are exactly the same as in Example 1.

[0083] Comparative Example 9 This comparative example provides a process for preparing petrolatum nanoemulsion. The difference from Example 1 is that in S4, the mass ratio of petrolatum to aqueous solution is adjusted to 1:5, while other operating parameters and process steps are exactly the same as in Example 1.

[0084] Comparative Example 10 This comparative example provides a process for preparing petrolatum nanoemulsion. The difference from Example 1 is that in S4, the mass ratio of petrolatum to aqueous solution is adjusted to 1:25. Other operating parameters and process steps are exactly the same as in Example 1.

[0085] The average particle size, particle size distribution, storage stability, and moisturizing properties of the petrolatum nanoemulsions prepared in Examples 1-5 and Comparative Examples 1-10 were tested. The specific test steps are as follows: (1) Average particle size and particle size distribution: Referring to the national standard GB / T 29022-2021 "Dynamic light scattering method (DLS) for particle size analysis", the petrolatum nanoemulsions prepared in Examples 1-5 and Comparative Examples 1-10 were placed in a dynamic light scattering particle size analyzer to measure the average particle size and polydispersity index (PI).

[0086] (2) Storage stability: The petrolatum nanoemulsions prepared in Examples 1-5 and Comparative Examples 1-10 were placed in a constant temperature incubator at an ambient temperature of 50°C and a relative humidity of 50% for 1 month (30 days). After 1 month, they were taken out and the average particle size and polydispersity index of the emulsion were remeasured.

[0087] (3) Moisturizing performance: The cellulose acetate filter membrane was immersed in a saturated magnesium nitrate solution at 25°C for 24 hours. After immersion, the membrane was removed and weighed, and recorded as W0. 100 μL of petrolatum nanoemulsion was pipetted onto the surface of the cellulose acetate filter membrane and placed in a constant temperature and humidity chamber at 25°C and 40% relative humidity for 8 hours. After immersion, the membrane was removed and weighed, and recorded as W0. t The moisture retention rate (%) is calculated using the following formula: Moisturizing rate (%) = [(W t -W0) / W0]×100%.

[0088] The test results are shown in Table 1.

[0089] Table 1. Test results of the petrolatum nanoemulsions prepared in Examples 1-5 and Comparative Examples 1-10

[0090] The test data from Example 1, Comparative Example 1, and Comparative Example 2 show that the amount of PVP added in Comparative Example 1 was too low, resulting in incomplete surface coverage of the nano-silica, easy particle aggregation, increased average droplet size of the emulsion, increased polydispersity index, poorer storage stability, and reduced moisture retention. In Comparative Example 2, the amount of PVP added was too high; the free PVP molecules caused bridging flocculation, leading to increased average droplet size of the emulsion, increased polydispersity index, and poorer storage stability.

[0091] The test data from Examples 1, 3, and 4 show that in Comparative Example 3, the addition amounts of polyvinylpyrrolidone and polyethylene glycol 400 were too low, resulting in incomplete coating of the silica surface, a large exposed area, severe particle agglomeration, increased average droplet size, higher polydispersity index, poorer storage stability, and reduced moisture retention. In Comparative Example 4, the addition amounts of polyvinylpyrrolidone and polyethylene glycol 400 were too high. Due to competitive adsorption of free polymers, the emulsification of hydrogenated lecithin was interfered with, leading to increased average droplet size, higher polydispersity index, poorer storage stability, and reduced moisture retention.

[0092] The test data from Examples 1, 5, and 6 show that in Comparative Example 5, the amount of hydrogenated lecithin added was too low, resulting in incomplete oil-water interface coverage and an inability to effectively reduce interfacial tension. During high-pressure homogenization, droplets easily coalesced, ultimately leading to an increase in the average droplet size, polydispersity index, poorer storage stability, and reduced moisturizing rate. In Comparative Example 6, the amount of hydrogenated lecithin added was too high. The free molecules formed micelles, competing for interfacial adsorption, resulting in an increase in the average droplet size, polydispersity index, poorer storage stability, and reduced moisturizing rate.

[0093] The test data from Examples 1, 7, and 8 show that in Comparative Example 7, the amount of modified silica dispersion added was too low, resulting in insufficient mechanical strength of the composite interfacial film at the oil-water interface. This inadequate support of the oil-water interface led to an increase in the average particle size of the emulsion droplets, a higher polydispersity index, poorer storage stability, and a lower moisture retention rate. In Comparative Example 8, the amount of modified silica dispersion added was too high, causing particle agglomeration and competitive adsorption, which affected the emulsification effect of hydrogenated lecithin. This resulted in an increase in the average particle size of the emulsion droplets, a higher polydispersity index, poorer storage stability, and a lower moisture retention rate.

[0094] The test data from Examples 1, 9, and 10 show that in Comparative Example 9, the amount of aqueous solution added was too low, the petrolatum content was too high, the oil-water interface coverage was insufficient, and the emulsion was unstable. Although the moisturizing rate did not decrease significantly, the average particle size of the emulsion droplets increased, the polydispersity index rose, and the storage stability deteriorated. In Comparative Example 10, the amount of aqueous solution added was too high, the petrolatum content was too low, and the moisturizing rate decreased significantly.

[0095] The applicant declares that the above description is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention fall within the protection and disclosure scope of the present invention.

Claims

1. A process for preparing a petrolatum nanoemulsion, characterized in that, The preparation process includes: S1. Polyvinylpyrrolidone and polyethylene glycol are dissolved in deionized water, wherein the polyethylene glycol is polyethylene glycol 400, and the mass ratio of polyvinylpyrrolidone to polyethylene glycol 400 is 2:1 to 3:

1. After stirring and heating, a polymer solution is obtained; nano-silica powder is dispersed in deionized water to obtain a silica dispersion. S2. Under stirring conditions, the polymer solution is dropped into the silica dispersion. The total mass ratio of the polyvinylpyrrolidone and polyethylene glycol 400 to the mass ratio of the nano silica powder is 1.5:1 to 2.5:

1. After mixing evenly, acid solution is dropped into the solution to adjust the pH value. Then, the solution is dispersed at high speed and stirred to mature, thereby obtaining the modified silica dispersion. S3. Hydrogenated lecithin and glycerol are dissolved in deionized water, wherein the mass ratio of hydrogenated lecithin to glycerol is 6:1 to 8:

1. After stirring and heating, a mixed solution is obtained. Under stirring and heating conditions, the modified silica dispersion is added to the mixed solution, wherein the mass ratio of the modified silica dispersion to the mixed solution is 2:1 to 4:

1. After mixing evenly, an aqueous solution is obtained. S4. Under stirring and heating conditions, molten petrolatum is added to the aqueous phase solution to obtain a crude emulsion, wherein the mass ratio of petrolatum to the aqueous phase solution is 1:10 to 1:20; under heating conditions, the crude emulsion is homogenized and stirred and matured to obtain the petrolatum nanoemulsion.

2. The preparation process of a petrolatum nanoemulsion according to claim 1, characterized in that, In S1, The stirring and heating temperature of the polyvinylpyrrolidone, polyethylene glycol and deionized water is 40~50℃; The stirring and heating speed of the polyvinylpyrrolidone, polyethylene glycol and deionized water is 300~500 rpm; The stirring and heating time for the polyvinylpyrrolidone, polyethylene glycol, and deionized water is 40-60 minutes. The total mass fraction of polyvinylpyrrolidone and polyethylene glycol in the polymer solution is 2-3 wt%.

3. The preparation process of a petrolatum nanoemulsion according to claim 1, characterized in that, In step S1, the nano-silica powder is dispersed in deionized water and stirred at a stirring speed of 3000~5000 rpm for 30~40 min to obtain the silica dispersion. The mass fraction of nano-silica powder in the silica dispersion is 3~5wt%.

4. The preparation process of a petrolatum nanoemulsion according to claim 1, characterized in that, In step S2, the polymer solution is added dropwise to the silica dispersion at a stirring speed of 500-600 rpm. After the polymer solution is added, the mixture is stirred for 10-20 minutes. Then, acid is added dropwise to the resulting mixed solution to adjust its pH value to 5-6. The acid solution is a citric acid solution with a mass fraction of 5-10 wt%. The high-speed dispersion rotation speed is 5000~8000 rpm; The high-speed dispersion time is 3-5 minutes; The stirring and maturation speed is 200~300 rpm; The stirring and maturation time is 40-50 minutes.

5. The preparation process of a petrolatum nanoemulsion according to claim 1, characterized in that, In S3, The hydrogenated lecithin, glycerol, and deionized water are stirred and heated at a temperature of 70~80℃; The stirring and heating speed of the hydrogenated lecithin, glycerol and deionized water is 300~500 rpm; The hydrogenated lecithin, glycerol, and deionized water are stirred and heated for 20-30 minutes. The total mass fraction of hydrogenated lecithin and glycerol in the mixed solution is 10-20 wt%.

6. The preparation process of a petrolatum nanoemulsion according to claim 1, characterized in that, In step S3, the modified silica dispersion is added to the mixed solution at a stirring speed of 300-500 rpm and a heating temperature of 70-80°C. After the modified silica dispersion is completely added, stirring and heating are continued for 20-30 minutes to obtain the aqueous solution.

7. The preparation process of a petrolatum nanoemulsion according to claim 1, characterized in that, In S4, the melting temperature of the petroleum jelly is 70~80℃; The melting time of the petrolatum is 20-30 minutes; At a stirring speed of 3000~5000 rpm and a heating temperature of 70~80℃, molten petroleum jelly is added to the aqueous solution. After all the petroleum jelly has been added, stirring and heating are continued for 5~10 minutes to obtain the crude emulsion.

8. The preparation process of a petrolatum nanoemulsion according to claim 1, characterized in that, In S4, the homogenization of the crude emulsion is high-pressure homogenization, and the pressure of the high-pressure homogenization is 80~120MPa; The homogenization temperature of the crude emulsion is 40~50℃; The crude emulsion is homogenized 3 to 5 times; The temperature for stirring and maturation is 20~30℃; The stirring and maturation speed is 200~300 rpm; The stirring and maturation time is 2-4 hours.

9. A petrolatum nanoemulsion, characterized in that, The petrolatum nanoemulsion is prepared using the preparation process described in any one of claims 1 to 8.

10. The application of the petrolatum nanoemulsion as described in claim 9 in the preparation of personal care products, characterized in that, The personal care products include body care products and facial care products.

Citation Information

Patent Citations

  • Silanization polymer emulsion and preparation method and application thereof

    CN101346435A

  • High-temperature-resistant water-based silicon dioxide dispersion liquid as well as preparation method and application thereof

    CN117004341A